Findings on interval colonoscopies: an auditable performance indicator for colonoscopy quality?. Issue 4 (30th April 2014) - Vaughan-Shaw, P G; Aung, M; Sahnan, K; Rai, P; Goodman, A
Abstract : Objective: An important marker of colonoscopy quality is detection of pathology and incidence of missed pathology. Back-to-back colonoscopies cannot ethically be performed for quality assurance alone yet may be required for clinical reasons. This study aims to investigate the incidence of new findings in colonoscopies repeated within a 12 month period and considers the role of such an analysis in the assessment of colonoscopy quality. Design: All colonoscopies performed over a 3-year period at an endoscopy training unit were studied. Colonoscopies repeated within a 12-month period were analysed. Results: 5747 colonoscopies were performed over the study period. 137 repeat colonoscopies were included with median interval from initial colonoscopy of 174 days. 19 (14%) repeat colonoscopies yielded new findings including one cancer, 234 days following a normal colonoscopy. Additional polyps were identified in 13 colonoscopies indicating a missed polyp rate of 9%. In these, a median number of two polyps per colonoscopy with median size 5.5 mm were found. There was no morbidity associated with repeat colonoscopy in this series. New findings on repeat colonoscopy appeared more likely following initial colonoscopy by non-consultant non-training grade endoscopists (23% vs 11%, p=0.09) yet small numbers involved preclude meaningful comparison. Conclusions: Analysis of clinically indicated repeat colonoscopies and rate of detection of new pathology may offer utility in colonoscopy quality assurance and would offer a direct assessment of the most important aspect of colonoscopy quality.